Circulating Tumor Cells: From Theory to Nanotechnology-Based Detection - Ming, Yue; Li, Yuanyuan; Xing, Haiyan; Luo, Minghe; Li, Ziwei; Chen, Jianhong; Mo, Jingxin; Shi, Sanjun (Frontiers in Pharmacology, 2017)
Cancer stem cells (CSCs) with stem-cell properties are regarded as tumor initiating cells. Sharing stem-cell properties, circulating tumor cells (CTCs) are responsible for the development of metastasis, which significant affects CTC analysis in clinical practice. Due to their extremely low occurrence in blood, however, it is challenging to enumerate and analyze CTCs. Nanotechnology is able to address the problems of insufficient capture efficiency and low purity of CTCs owing to the unique structural and functional properties of nanomaterials, showing strong promise for CTC isolation and detection. In this review, we discuss the role of stem-like CTCs in metastases, provide insight into recent progress in CTC isolation and detection approaches using various nanoplatforms, and highlight the role of nanotechnology in the advancement of CTC research.